Pseudomonas aeruginosa bacteremia and prostatitis in a patient with cystic fibrosis - Anand, Anju (Canadian Medical Association, 2013)
Patients with cystic fibrosis (CF) commonly suffer chronic respiratory infections, although systemic dissemination is relatively rare. Acute bacterial prostatitis presents dramatically and is believed to be mostly caused by local migration (with or without instrumentation) of the lower urinary tract and presents with a predictable microbial etiology. We report a case of a 26-year-old man presenting with acute Pseudomonas aeruginosa bacterial prostatitis due to hematogenous propagation from a chronic pulmonary infection.